Genomic analysis and characterization of lytic bacteriophages that target antimicrobial resistant Escherichia coli in Addis Ababa, Ethiopia - Tamirat Salile Sada; Dawit Hailu Alemayehu; Kalkidan Melaku Tafese; Tesfaye Sisay Tessema (Heliyon)
The emergence of antibiotic resistance in E. coli strains has sparked a fervent investigation of alternative therapies, such as the use of lytic bacteriophages. Phage genome sequence analysis is a novel method for learning more about proteins and other biomolecules encoded by phages, particularly phage-lytic enzymes that are crucial to the lysis of bacterial cells. Seven potential lytic E. coli phages—EH-B-A (A1), EP-M-A, EP-B-K (E2), EI-SP-GF, ET-SD-TH, and ST-TK—isolated from activated dairy farm sludges, rivers, and hospital liquid waste genomes were described in this study. The Illumina NextSeq 550 sequencer was used for sequencing phage isolates. The virus nucleotide collection (nr/nt) (taxid:10239) was used to evaluate whole-genome sequences. Phylogenetic analysis was performed using the MEGA11 software. Genome sequencing revealed that each bacteriophage contained a linear double-stranded DNA genome. Phage isolates were taxonomically identified as the Caudoviricetes class with four genera of phages, including Kagunavirus, Vequintavirus, Dhillonvirus, and Jilinvirus. Phage genome lengths varied from 24,264 to 136,204 bp, and GC contents ranged from 44 % to 55 %. In total, 33–218 CDSs (coding sequences) were predicted, with 19–77 % of CDSs encoding functional proteins. All phages lacked tRNA genes in their genomes, except for EI-SP-GF, which possessed five tRNA genes. Based on the phylogenetic tree analysis, the phage isolates were related to Enterobacteria and E. coli phage sequences in the database. Screening did not show any genes encoding for a CRISPR-like system, virulence, antibiotic resistance, or lysogeny. Because of their stringent lytic nature, these phage isolates might be used in the future to treat E. coli infections. This study might also provide some primary data for developing phage control techniques and advance our understanding of the genetic composition of E. coli phages.